Artificial intelligence for legal security. Overcoming the problem of the cognoscibility of law - Peña Carlos, Jhonatan Samuel (2022)
Persons find it difficult to know, identify and understand legal provisions, which being abundant coexist with the fluctuating case law, the doctrine, among other legal cognitive inputs. In view of the foregoing, this research attempts to overcome the problem of the cognoscibility of law through two practical applications of artificial intelligence – expert informative and cognitive legal systems – with the aim of ensuring better conditions of access, identification and comprehension of the law, by all persons, to suitably channel their behaviors. This scenario manages to configure a new interaction between the legal information and the persons, to attain further knowledge of the law as an ideal condition of legal security.